Gynaecology today a textbook of gynaecology - Sivalingam Nalliah; Kavitha Nagandla; Mohamed Najimudeen (Colour Box Publishing House, 2012)
GYNAECOLOGY TODAY is a comprehensive evidence based textbook, written with a easy to read format, using simple language and comprehensively formatted with consistent headings which makes locating information easier. All chapters include one or two clinical scenarios for students to appreciate the clinical application of facts and conclude with a boxed KEY FACTS as 'take-home messages'. The prime objective is to dispel fears and perception that Gynaecology is more difficult to comprehend when compared to Obstetrics